Motivasi Belajar Mahasiswa Pendidikan Kesehatan Dan Rekreasi FKIP UNRI Tahun 2019 Melalui Media Google Kelas Di Saat Pandemi Covid 19 - Yudhitira, Eryanda; Ramadi, Ramadi; Vai, Aref; Ittaqwa, Ittaqwa (Jurnal Inovasi Olahraga, 2022)
The constraint this research is that learning motivation of physical education students during the Covid-19 pandemic through the Google Classroom media is very lacking. The aim is to find out the learning motivation of students in Physical Education, Health and Recreation, Class of 2019 FKIP UNRI. The population and sample in this research were students of Penjaskresek's Classes A and B of 2019 using a total sampling technique of 78 students. The instrument of this research used a questionnaire and student semester scores. Based on the results of data analysis and discussion, it is obtained as follows: The average attention factor in the pass category is in the range of 55.32%. relevance factor) then the average in the sufficient category is in the range of 61.70%. The confidence factor means that the average in the category less is in the range of 57.45%. Satisfaction factor then the average in the sufficient category is in the range of 65.95%. That the learning motivation of physical education, health and recreation students for the 2019 FKIP UNRI through Google Classroom media during the Covid-19 period was in the sufficient category or at 61.70%.